Independent Semantic and Syntactic Representations in L2 Mandarin Learners: Evidence from Structural Priming - Douglas J. Getty; Xiang Wei; Lin Chen (MDPI AG, 2024)
Structural representations in English have been shown to be quite abstract, with structural information being represented independently from semantic information. Mandarin has a relatively sparse marking of syntactic information, with no inflections for case, number, or tense. Given this syntactic sparsity, Huang et al. (2016) hypothesized that, distinct from English-language findings, Mandarin learners may have shared syntactic and semantic representations, such that semantic information can guide structure building. We examined this question in L2 Mandarin learners using a structural priming paradigm that required reading Mandarin primes. We found that L2 Mandarin learners exhibit within-language structural priming, and this effect is independent of semantic information. These findings have two implications: (1) this represents the first demonstration of within-language L2 Mandarin structural priming; (2) L2 learners can develop syntactic representations independent of semantic representations, even when the target L2 language lacks rich marking of syntactic information.